Peningkatan Kemampuan Koneksi Matematika Melalui Pembelajaran Matematika RealistikEKSI MATEMATIKA MELALUI PEMBELAJARAN MATEMATIKA REALISTIK - Evayanti, Sri; Munir, Nilam Permatasari (Journal of Mathematics Learning Innovation, 2023)
This research aims to determine whether mathematical connection abilities can be improved through realistic mathematics learning. This type of research is classroom action research. The PTK model used is the Kemmis and Taggart model which consists of 4 stages, namely planning, implementation, observation, and reflection. The subjects of this research were students in class VIII.1 of SMP Negeri 2 Belopa in the odd semester of the 2022/2023 academic year with a total of 23 students. This research was carried out in two cycles, each cycle was held in 3 meetings. There were two research instruments used, namely a mathematical connection ability test sheet and an observation sheet of student and teacher activities. The data collection techniques used are test, observation and documentation techniques. The data used in this research was analyzed quantitatively and qualitatively. The results of the observations were analyzed qualitatively, while for quantitative analysis descriptive analysis was used consisting of the calculated average (mean), maximum value and minimum value obtained by students in each cycle. The research results showed that the average score of students after implementing realistic mathematics learning in cycle I was that their mathematical connection ability was in the very poor category, namely 30%, while in cycle II, students' mathematical connection ability was in the very good category, namely 91%. The results of observing student activities in cycle I were 59% in the sufficient category, while in cycle II it increased to 88% in the very good category. The results of learning management observations in cycle I were 75% in the good category and in cycle II it increased to 85% in the very good category. So it can be concluded that mathematical connection abilities through realistic mathematics learning in class VIII SMP Negeri 2 Belopa can be improved.